EVALUATION AND COMPARISON OF CYTOTOXIC EFFECT OF VILAZODONE HYDROCHLORIDE WITH 5-FLUOROURACIL IN HT-29 BOWEL CANCER CELL LINE - PRIYA A, LATHA; D, ANUSHA; CHELLATHAI K, DARLING; A, HEMALATHA; MOHAN Y, JEGAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Vilazodone hydrochloride is a novel selective serotonin reuptake inhibitor (SSRI) used to treat major depressive disorders. There are only sparse data available to know about the SSRI’s and its association with colon cancer. This study aims to evaluate and compare the in vitro cytotoxic effect of vilazodone with 5-fluorouracil (5-FU) in HT-29 cell line. Methods: Cell viability was tested by the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay (Mosmann, 1983). Test sample and standard drug in variable concentrations were added to the HT-29 cell lines for incubation over 24 h under ideal conditions. After washing the test and standard drug sample from the well with saline, MTT was added and incubated for 4 h. Dimethyl sulfoxide of 1 ml was added in all wells after incubation with MTT. The absorbance at 570 nm was measured with an ultraviolet - spectrophotometer. Results: The values were tabulated, and the graph was plotted to find the IC-50 value (inhibitory concentration at 50%) which was struck at 28.5 μg/ml and12. 8 μg/ml for vilazodone hydrochloride and 5-FU, respectively. Conclusion: The results show that vilazodone hydrochloride has good anticancer property comparable with 5-FU, which would probably play a role as a cytotoxic agent in tumor cells. The proposed mechanism of action could be by activation of caspase-3 enzyme, thereby increasing apoptosis and indicates its use in coexisting depression and colon carcinoma. Other mechanism includes suppression of oncogene p53, which can be confirmed by future studies.